RADIO IDOLA SEMARANG ACTIVITIES TO BUILD BRAND ENGAGEMENT IN LISTENERS - RR. VASHNI EUODIA TUSTASATYA; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Radio Idola is one of the private radio News and Talk in Semarang, which has a very diverse audience (heterogeneous). In 2016 the fourth wave according to the Nielsen survey, radio Idola is the only radio News & Talk, which is ranked the top 10 best radio in the city of Semarang. The study aimed to find out how is the activities of radio Idola to build brand engagement on the listeners. This study used a descriptive qualitative approach with post-positivism paradigm to help analyze and find facts based on reality. This study uses a case study approach, using the Mass Communication theory, the theory of Technological Determinism, Radio Programming and Brand Engagement. The study was conducted to seven informants who are internal staff of radio Idola Semarang. The first results of radio Idola activities to build brand engagement is listening and monitoring. This activity is about the capability of radio Idola to create a new culture of mutual guide and help fellow listeners through the power of social media and instant messaging owned. Radio Idola as a communicator has a function to inform the listeners quickly and precisely, radio Idola also be channeling public opinion, media persuasion, educate and entertain. Radio Idola accept any public complaints related to public services around. Secondly, community management show that any program that is on the radio Idola is derived from the tagline Memandu & Membantu. The programming process of radio Idola is done through planning, production, execution, monitoring and evaluation. The listeners are very well demonstrated by the presence of the audience at each of off-air even radio Idola held in the end of the month which always achieve the target. Third, community participation show that Radio Idola has a special Whatsapp group listeners and has 37.759 listeners who join in their fan page facebook. Listeners can participate in on air program to speak their mind also give the positive comments about their services in social media. Identify Advocates show that radio Idola has loyal listeners in overseas that still listening radio Idola via streaming. Radio Idola has not had a brand ambassador who comes from a loyal listener to be representative in order to introduce a wider radio Idola as a brand.